Five‐year efficacy and safety of tenofovir‐based salvage therapy for patients with chronic hepatitis B who previously failed LAM/ADV therapy. (22nd December 2016) - Lim, Lucy; Thompson, Alexander; Patterson, Scott; George, Jacob; Strasser, Simone; Lee, Alice; Sievert, William; Nicoll, Amanda; Desmond, Paul; Roberts, Stuart; Marion, Kaye; Bowden, Scott; et al.
Abstract: Background: Multidrug‐resistant HBV continues to be an important clinical problem. The TDF‐109 study demonstrated that TDF±LAM is an effective salvage therapy through 96 weeks for LAM‐resistant patients who previously failed ADV add‐on or switch therapy. We evaluated the 5‐year efficacy and safety outcomes in patients receiving long‐term TDF±LAM in the TDF‐109 study. Methods: A total of 59 patients completed the first phase of the TDF‐109 study and 54/59 were rolled over into a long‐term prospective open‐label study of TDF±LAM 300 mg daily. Results: Results are reported at the end of year 5 of treatment. At year 5, 75% (45/59) had achieved viral suppression by intent‐to‐treat analysis. Per‐protocol assessment revealed 83% (45/54) were HBV DNA undetectable. Nine patients remained HBV DNA detectable, however 8/9 had very low HBV DNA levels (<264IU/mL) and did not meet virological criteria for virological breakthrough (VBT). One patient experienced VBT, but this was in the setting of documented non‐compliance. The response was independent of baseline LAM therapy or mutations conferring ADV resistance. Four patients discontinued TDF, one patient was lost to follow‐up and one died from hepatocellular carcinoma. Conclusions: Long‐term TDF treatment appears to be safe and effective in patients with prior failure of LAM and a suboptimal response to ADV therapy. These findings confirm that TDF has a high genetic barrier to resistance is active against multidrug‐resistant HBV, and should be the preferred oral anti‐HBV agent in CHB patients who fail treatment with LAM and ADV.